Comparative analysis of nucleic acid sequences by their general constraints. - Lipman, D J (1982)
We describe two measures of a nucleic acid sequence, derived from Information Theory, which characterize the constraints toward nonuniform base composition, and the constraints on the ordering of the bases. These two measures distinguish extra-chromosomal coding sequences from all other coding sequences examined. The two measures separate eukaryotic coding sequences into two groups: those with introns and those without introns. We have also found a relationship between the general constraints of a subsequence and its degree of conservation in related genes.